Diseño gráfico como herramienta en la creación de recursos didácticos dirigidos a niños con trastorno de espectro autista nivel 1 del centro integral de terapias casa oruga en la ciudad de Ibarra - Delgado Lopez, Bryan Santiago (2024)
This project focuses on the development of specialized didactic materials for children with Level 1 Autism Spectrum Disorder (ASD) at the Casa Oruga Integral Therapies Center. The objective is to improve the communication and learning of these children by adapting didactic resources to meet their specific needs. The project addresses the lack of adequate didactic materials, highlighting the importance of adapting these resources to foster better understanding, participation, and independence in children with ASD through playful activities, allowing for more effective progress in children and reinforcing competitiveness and social interaction.